2023
DOI: 10.1186/s12887-023-03966-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between diet quality scores and risk of overweight and obesity in children and adolescents

Abstract: Background This study examined the associations of diet quality assessed by Healthy Eating Index 2015 (HEI-2015), Alternative Healthy Eating Index 2010 (AHEI-2010), Mediterranean Diet (MedDiet) and overweight/obesity in children and adolescents. Methods This cross-sectional study used data of participants aged 2–19 years from National Health and Nutrition Examination Survey (NHANES) 2005–2018. The weighted logistic regression model was adopted to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In agreement with our study, the ToyBox-study has indicated that the proportion of pre-school children having a low Diet Quality Index (DQI), not adapting to both step and screen time (ST) references was very high, and it was related with an increased likelihood of being affected by overweight or obesity [ 66 ]. A cross-sectional study evaluating data from the National Health and Nutrition Examination Survey (NHANES) has shown that greater MD adherence was significantly related with a lower risk of childhood overweight and obesity; however, the enrolled children had a broad range of ages from 2 to 11 years old [ 67 ]. Moreover, in a Spanish population of pre-school children aged 4–5 years old, a higher adherence of children to the MD was independently associated with breastfeeding for at least 6 months compared to their peers who were never breastfed [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our study, the ToyBox-study has indicated that the proportion of pre-school children having a low Diet Quality Index (DQI), not adapting to both step and screen time (ST) references was very high, and it was related with an increased likelihood of being affected by overweight or obesity [ 66 ]. A cross-sectional study evaluating data from the National Health and Nutrition Examination Survey (NHANES) has shown that greater MD adherence was significantly related with a lower risk of childhood overweight and obesity; however, the enrolled children had a broad range of ages from 2 to 11 years old [ 67 ]. Moreover, in a Spanish population of pre-school children aged 4–5 years old, a higher adherence of children to the MD was independently associated with breastfeeding for at least 6 months compared to their peers who were never breastfed [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research also suggests that it has a protective effect against childhood overweight/obesity [ 9 , 10 , 11 ]. In pregnancy, closer maternal adherence to the MedDiet has been inversely associated with potential risk factors for childhood obesity in early life, such as preterm delivery [ 12 ], fetal growth restriction [ 13 ], and small-for-gestational-age (SGA) infants at birth [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Higher AHEI scores were associated with lower risk of major chronic diseases (cardiovascular disease, diabetes, colorectal and breast cancer) and lower overall mortality [ 9 ]. AHEI-2010 has been widely used in China to evaluate the dietary quality of different diseases and populations [ 10 14 ]. In this study, we attempted to explore specific dietary patterns and behaviors associated with stroke risk.…”
Section: Introductionmentioning
confidence: 99%